Evaluation of Sapota (Manilkara achrar (Mill) Forberg) for Postharvest Qualities - Maya T (Department of Processing Technology, College of Horticulture, 1999)
A study on the screening of post-harvest qualities of five varieties of sapota grown In the college orchard was conducted at the Department of Processing Technology, College of Horticulture, Vellanikkara during 1998-99. On screening varieties like 'Cricket Ball', 'Co-I', 'Co-2', 'PKM l' and 'Oval' for physical, chemical and sensory parameters, 'Co-2', 'PKM l ' and 'Oval' were rated best for table purpose, while 'Co-2' for distant marketing and 'Co-I' for processing qualities. Individually wrapping the fruits with cling film, or packaging fruits with 30 per cent moistened saw dust was evolved as the best storage technique to extend the shelf-life of sapota at ambient temperature. Saw dust being cheap, and less labour intensive can be suggested as an appropriate storage technique at field level without the involvement of any chemical, electricity or civil structure, while cling wrap can be aimed for retail marketing. Osmotic dehydration of sapota slices of thickness 0.5 to 1 cm using dry sugar containing 1500 ppm S02 and 0.3 per cent citric acid in a ratio of 1: 1 for eight hours followed by oven drying took only 16 hours to accomplish the drying unlike the reported 33 hours of osmo-air drying. Thus the technique developed can improve the quality of the product many fold and can reduce the energy consumption considerably.